'Just let them play': Complex dynamics in youth sport, why it isn't so simple - Nash, C.; Taylor, J. (Frontiers in Psychology, 2021)
This ethnographic case study examines the long-term impact of youth sport coaching within tennis, using observations, field notes, and interviews as data sources. We highlight the complexities that youth sport coaches face in their role in developing young players within, in this example, tennis, but suggest that these issues are transferable across the youth sport context. There are some key messages for youth sport coaches and sporting organisations arising from this study, particularly around the role of a youth sport coach. We advocate an expertise approach to developing youth sport coaches due to the many roles, within their sport and from a biopsychosocial perspective, that they have to navigate. Additionally, we suggest that simplistic narratives in youth sport coaching are misplaced.